Pengembangan bahan ajar bahasa Sasak berbasis high order thingking skills - Taufiqqurrahman Taufiqqurrahman; Mohammad Efendi; Sulton Sulton (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
The research objective is to produce and test the feasibility of textbooks based Sasak language thingking high order skills for junior high school students. The model used is a model development Dick, Carey & Carey until the ninth stage. The product development is validated by subject matter experts with the level of validity 73%, media expert with a degree of validity of 84%, a learning design with a level of validity 90.4%, individual testing with a level of validity to 68%, small group trial with a level of validity 82% and test field trials with a validity rate of 89% with a very worthy qualification does not need revision.Keywords: Development of Learning Material, Language Sasak, High Order Thingking Skills http://dx.doi.org/10.17977/um022v2i12017p015